2016
DOI: 10.1074/jbc.m115.697011
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestine but Not Liver Lysophosphatidylcholine Acyltransferase 3 (Lpcat3) Deficiency Has a Dominant Effect on Plasma Lipid Metabolism

Abstract: Lysophosphatidylcholine acyltransferase 3 (Lpcat3) is involved in phosphatidylcholine remodeling in the small intestine and liver. We investigated lipid metabolism in inducible intestine-specific and liver-specific Lpcat3 gene knock-out mice. We produced Lpcat3-Flox/villin-Cre-ER T2 mice, which were treated with tamoxifen (at days 1, 3, 5, and 7), to delete Lpcat3 specifically in the small intestine. At day 9 after the treatment, we found that Lpcat3 deficiency in enterocytes significantly reduced polyunsatura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 38 publications
(58 reference statements)
2
30
0
1
Order By: Relevance
“…Notably, recent reports consistently demonstrate that liverspecific gene deletion of the related Mboat5 (Lpcat3) exacerbates hepatic inflammation and macrophage infiltration, whereas it has no significant effect on lipid accumulation when mice are fed normal chow. (36,37) In toto, this suggests that inflammation is the driver for MBOAT7-mediated fibrosis, a hypothesis consistent with all published data. (3)(4)(5)(6) Interestingly, similar to earlier reports, (13,17) we show that neither PNPLA3 nor TM6SF2, both implicated in hepatic lipid trapping, had any significant influence on liver damage in CHB.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Notably, recent reports consistently demonstrate that liverspecific gene deletion of the related Mboat5 (Lpcat3) exacerbates hepatic inflammation and macrophage infiltration, whereas it has no significant effect on lipid accumulation when mice are fed normal chow. (36,37) In toto, this suggests that inflammation is the driver for MBOAT7-mediated fibrosis, a hypothesis consistent with all published data. (3)(4)(5)(6) Interestingly, similar to earlier reports, (13,17) we show that neither PNPLA3 nor TM6SF2, both implicated in hepatic lipid trapping, had any significant influence on liver damage in CHB.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, as positive control, both PNPLA3 and TM6SF2 had an association with steatosis in CHB, implying that the impact of rs641738 on steatosis is likely marginal. Notably, recent reports consistently demonstrate that liver‐specific gene deletion of the related Mboat5 ( Lpcat3 ) exacerbates hepatic inflammation and macrophage infiltration, whereas it has no significant effect on lipid accumulation when mice are fed normal chow . In toto , this suggests that inflammation is the driver for MBOAT7‐mediated fibrosis, a hypothesis consistent with all published data …”
Section: Discussionmentioning
confidence: 99%
“…The ABCA1 transporter is responsible for the formation of pre‐β HDL on the enterocytes basal side . In good agreement with Kabir et al., our results show that HL induces a fall of ABCA1 expression in the SI . In the present study, we have proven for the first time that the administration of GIN causes the increase of ABCA1 protein levels in the SI, and thus may contribute to the increased production of pre‐β HDL.…”
Section: Discussionsupporting
confidence: 55%
“…Studies from the Tontonoz laboratory yielded similar results, with additional observations that identified a mechanism related to reduced production of arachidonoyl phospholipids and the remodeling of enterocyte plasma membrane phospholipid composition being the gatekeeper important for passive lipid absorption and chylomicron production [**11,**12]. Although results from these studies have led to the suggestion that inhibiting intestinal LPCAT3 activity may be a novel approach for treatment of dietary lipid-associated hyperlipidemia and metabolic disorders [**10,**12], the desirability of this strategy requires extensive and detailed exploration considering that intestinal LPCAT3 activity appears to be required for survival of mice on lipid-rich diets and its inactivation causes the undesirable effects of food intake cessation and starvation [**12]. …”
Section: Intestinal Lysophosphatidylcholine and Chylomicron Biosynthesismentioning
confidence: 86%
“…The Jiang laboratory showed that the lack of LPCAT3 expression lower plasma levels of cholesterol, phospholipid, and triglyceride due to reduced lipid absorption [9]. Subsequent studies from the same laboratory documented that the dominant effect of LPCAT3 deficiency on plasma lipid levels is due to its defective expression in the intestine while liver LPCAT3 deficiency only impacts on plasma triglyceride levels [**10]. Studies from the Tontonoz laboratory yielded similar results, with additional observations that identified a mechanism related to reduced production of arachidonoyl phospholipids and the remodeling of enterocyte plasma membrane phospholipid composition being the gatekeeper important for passive lipid absorption and chylomicron production [**11,**12].…”
Section: Intestinal Lysophosphatidylcholine and Chylomicron Biosynthesismentioning
confidence: 99%